Long-Term Follow-Up of Restorations of Equine Cheek Teeth Infundibula (2006–2017) - Pearce, Christopher J.; Brooks, Nicky (Frontiers in Veterinary Science, 2022)
Abnormalities of equine cheek teeth infundibula are common, mainly involving varying degrees of developmental hypocementosis and acquired caries. Consequences of infundibular caries includes fracture and / or apical infection. There are no published reports of long-term clinical follow-ups of infundibular caries treatment but anecdotally restoration of infundibular defects has been reported to prevent further caries. This paper is a retrospective study of restorations of carious infundibula using human dental restoratives, recording the occlusal appearance of the teeth and restorations at up to 6 years follow-up, and furthermore at up to 10 years follow-up. Results showed that restoration of carious infundibula using human dental restoratives can be recommended as a safe technique with long term retention of restorative material.